Some coincidence point results for T-contraction mappings on partially ordered b-metric spaces and applications to integral equations - Radenovic´, Stojan; An, Tran Van Van; Quan, Le Thanh Thanh (Nonlinear Analysis: Modelling and Control, 2017)
In this paper, we prove some fixed point results for T-contraction mappings in partially ordered b-metric spaces, that generalize the main results of [H. Huang, S. Radenovič, J. Vujakovič, On some recent coincidence and immediate consequences in partially ordered b-metric spaces, Fixed Point Theory Appl., 2015, Paper No. 63]. As an application, we discuss the existence for a solution of a nonlinear integral equation.
Keywords: b-metric; T-contraction; fixed point; integral equation